Effect Of Work Stress On Employee Productivity At Pt Unggul Karya In The Extruder Division - Destiana Kumala; Destiana Utarindasari; Kiki Joesyiana (International Journal of Sharia Business Management, 2022)
The term "working life balance" is becoming increasingly popular among the millennial generation; however, this situation cannot be separated from the high demands of the workplace on employee productivity as company resources. To address this issue, the author conducted a research study titled The Effect of Work Stress on Employee Productivity in the Extruder Division at PT Unggul Karya in Wanaherang, Bogor Regency. The authors use quantitative research methods to process data using descriptive statistical data analysis techniques, and linear regression shows the equation Y (productivity variable) = 41.045 + 0.606X (stress variable) influence of productivity with stress as x variable by employees of PT Unggul Karya's Extruder Division, while the correlation coefficient analysis with r count 0.71 and the coefficient of determination shows that productivity.